2016
DOI: 10.1186/s12958-016-0199-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of ATF6α in the mouse uterus during embryo implantation

Abstract: BackgroundATF6α, one of the sensor proteins in the stress signaling pathway of the endoplasmic reticulum, is located in the membrane of the endoplasmic reticulum. To date, the physiological function of ATF6α in the process of embryo implantation has not been reported.MethodsIn this study, the expression pattern of ATF6α in the mouse uterus during peri-implantation and the estrous cycle was detected by real-time PCR, western blot and immunohistochemistry.ResultsATF6α mRNA and protein levels were higher in the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Patients also exhibited foveal deficits, suggesting that ATF6 plays a crucial role in the development of the fovea and cone photoreceptors in humans [ 25 27 ] Early-onset photoreceptor degeneration ATF6 splice-variant mutations causing compromised photoreceptor function Nervous tissue Western blot analyses of glycosylated ATF6 expression in adult and embryonic mouse brains Compared to adult tissue, the expression of partially glycosylated ATF6 is elevated in the brains of mouse embryos [ 30 ] Olfactory sensory neurons Low-level expression (relative to ATF5) of ATF6 during development [ 32 ] Immunohistochemical staining of ATF6 (cytoplasmic and nuclear) in the developing rat cerebellum ATF6 was activated at postnatal day 7 (prior to the appearance of myelin), with maximal nuclear-localised ATF6 visualised at postnatal day 10 (onset of myelination) [ 33 ] Muscle OE of active ATF6 in myoblasts ↑ ATF6 ➔ ↓ Mcl-1 ➔ apoptotic myoblast cells. ATF6 may regulate muscle cell development through promoting post-translational modification of Mcl-1 [ 35 ] OE of DKK3 in mESCs Transient ATF6 overexpression or siRNA-mediated ATF6 KD at day 2 of ESC differentiation DKK3 induced differentiation of ESCs into smooth muscle cells (SMCs) ↑ ATF6 during DKK3-induced ESC-SMC differentiation OE and KD ➔ ATF6 is involved in DKK3-mediated SMC generation via ↑myocardin expression [ 36 ] Ovarian Tissue Analyses of ATF6 and associated markers during the bovine corpus luteum lifespan and in goat granulosa ATF6 and ATF4➔ ↑CHOP and ↑caspase-12 [ 37 39 ] Molecular and immunohistochemical detection of ATF6α during peri-implantation and the oestrous cycle in mice ↑ATF6α mRNA and protein in the d5 uterus close to the implantation site and in d7–8 secondary decidual zone; ATF6α expression affected by progesterone and estrogen in ovariectomised mice [ 40 ] Adipose Tissue KD of ATF6α in C3H10T1/2 cells ATF6α KD ➔ ↓ C3H10T1/2 differentiation and ↓ lipid accumulation [ 41 ] Glucose deprivation ↓SREBP2-mediated lipogenesis [ …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients also exhibited foveal deficits, suggesting that ATF6 plays a crucial role in the development of the fovea and cone photoreceptors in humans [ 25 27 ] Early-onset photoreceptor degeneration ATF6 splice-variant mutations causing compromised photoreceptor function Nervous tissue Western blot analyses of glycosylated ATF6 expression in adult and embryonic mouse brains Compared to adult tissue, the expression of partially glycosylated ATF6 is elevated in the brains of mouse embryos [ 30 ] Olfactory sensory neurons Low-level expression (relative to ATF5) of ATF6 during development [ 32 ] Immunohistochemical staining of ATF6 (cytoplasmic and nuclear) in the developing rat cerebellum ATF6 was activated at postnatal day 7 (prior to the appearance of myelin), with maximal nuclear-localised ATF6 visualised at postnatal day 10 (onset of myelination) [ 33 ] Muscle OE of active ATF6 in myoblasts ↑ ATF6 ➔ ↓ Mcl-1 ➔ apoptotic myoblast cells. ATF6 may regulate muscle cell development through promoting post-translational modification of Mcl-1 [ 35 ] OE of DKK3 in mESCs Transient ATF6 overexpression or siRNA-mediated ATF6 KD at day 2 of ESC differentiation DKK3 induced differentiation of ESCs into smooth muscle cells (SMCs) ↑ ATF6 during DKK3-induced ESC-SMC differentiation OE and KD ➔ ATF6 is involved in DKK3-mediated SMC generation via ↑myocardin expression [ 36 ] Ovarian Tissue Analyses of ATF6 and associated markers during the bovine corpus luteum lifespan and in goat granulosa ATF6 and ATF4➔ ↑CHOP and ↑caspase-12 [ 37 39 ] Molecular and immunohistochemical detection of ATF6α during peri-implantation and the oestrous cycle in mice ↑ATF6α mRNA and protein in the d5 uterus close to the implantation site and in d7–8 secondary decidual zone; ATF6α expression affected by progesterone and estrogen in ovariectomised mice [ 40 ] Adipose Tissue KD of ATF6α in C3H10T1/2 cells ATF6α KD ➔ ↓ C3H10T1/2 differentiation and ↓ lipid accumulation [ 41 ] Glucose deprivation ↓SREBP2-mediated lipogenesis [ …”
Section: Introductionmentioning
confidence: 99%
“…1 ). Moreover, documentations of increased ATF6α expression in murine uterine tissue suggested that ATF6 may also regulate embryo implantation and decidualisation (the process of forming decidua: the uterine lining during pregnancy and maternal part of placenta) [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ATF6 has been implicated in the development of multiple tissue types, and dysregulation of ATF6 expression is related to disease (Hillary and FitzGerald, 2018). Developmental roles of ATF6 include mesoderm differentiation (Kroeger et al, 2018), osteogenesis and chondrogenesis (Guo et al, 2016;Jang et al, 2012;Kim et al, 2014;Maeda et al, 2015;Xiong et al, 2015), neurodevelopment (Cho et al, 2009;Naughton et al, 2015;Saito et al, 2012;Zhang et al, 2007), adipogenesis and lipogenesis (Lowe et al, 2012), and formation of female reproductive structures (Lin et al, 2012;Park et al, 2013;Xiong et al, 2016;Yang et al, 2015). Most relevant to our work is the role of ATF6 in ocular and muscular embryology, because these tissues had the highest ATF6 reporter expression during zebrafish development.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ATF6 has been implicated in development of multiple tissue types, and dysregulation of ATF6 expression is related to disease (Hillary and FitzGerald, 2018). Developmental roles of ATF6 include mesoderm differentiation (Kroeger et al, 2018), osteogenesis and chondrogenesis (Guo et al, 2016; Jang et al, 2012; Kim et al, 2014; Maeda et al, 2015; Xiong et al, 2015), neurodevelopment (Cho et al, 2009; Naughton et al, 2015; Saito et al, 2012; Zhang et al, 2007) adipogenesis and lipogenesis (Lowe et al, 2012), and formation of female reproductive structures (Lin et al, 2012; Park et al, 2013; Xiong et al, 2016; Yang et al, 2015). Most relevant to our work is the role of ATF6 in ocular and muscular embryology, because these tissues had the highest ATF6 reporter expression during zebrafish development.…”
Section: Introductionmentioning
confidence: 99%